Experience in the study of religiosity in the Belarusian environment: sociological approaches - Shkurova, Alena V. (Journal of the Belarusian State University. Sociology, 2019)
The article presents the results of studying the peculiarities in the religiosity of the population in Belarus. The changes in the Belarusian society also affect the religious sphere. This requires the development of models for its scientific study. The characteristics of a religious field are reflected in the phenomenon of religiosity. Based on data from sociological studies of different years, it is possible to track its dynamics throughout the entire period of developing the Belarusian society. The assessment of religiosity is carried out on the basis of its most significant and comparable indicators: religious affiliation and ideological position. Their comparison demonstrates the quantitative stability of population confessional identification and changes in religiosity mainly within the framework of ideological types. The results of various studies confirm that this trend has persisted in the Belarusian society throughout almost the entire period of its development. This allows making a conclusion about transforming nature of religiosity and transiting to the phase of qualitative changes.
Keywords: religiosity; model of religiosity; religion; religious and ideological type; religious affiliation; degrees of religiosity; transformation of religiosity